2012
DOI: 10.1021/jp210405s
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Nature of Cationic Calix[6]arene Aqueous Solutions

Abstract: The study of the aqueous solutions of the cationic hexameric calixarene 5,11,17,23,29,38,39,40,41,42hexametoxycalix[6]arene hexachloride demonstrates their colloidal nature. Within the concentration range from 1 × 10 −5 to 0.01 M, this compound forms positively charged aggregates of a much larger size as compared with those of tetrameric cationic calix[4]arene previously studied by us. The aggregation was confirmed both by DLS and TEM experiments; the last method revealed that the 10 2 to 10 3 nm sized particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The observed 6 to 23 nm bathochromic shifts of the bands of the double charged anions of bromophenol blue, bromocresol green, bromocresol purple, fluorescein, sulfonefluorescein, aminofluorescein, and rose Bengal B (see ESI †) may be taken as a strong support for the positive interfacial charge of the colloidal species, because the same shifts are typical for these dyes in the presence of cationic surfactant micelles and aggregates of cationic dendrimers and calixarenes. 55,56 By contrast, the absorption band of the cationic dye pseudoisocyanine displays no shift in the presence of the ND particles; only small alteration of intensity is registered. These results support the significant role of the ND charge for adsorption of organic species such as fluorescent ions 21,27 and daunorubicin.…”
Section: Surface Charge Of the Colloidal Speciesmentioning
confidence: 94%
“…The observed 6 to 23 nm bathochromic shifts of the bands of the double charged anions of bromophenol blue, bromocresol green, bromocresol purple, fluorescein, sulfonefluorescein, aminofluorescein, and rose Bengal B (see ESI †) may be taken as a strong support for the positive interfacial charge of the colloidal species, because the same shifts are typical for these dyes in the presence of cationic surfactant micelles and aggregates of cationic dendrimers and calixarenes. 55,56 By contrast, the absorption band of the cationic dye pseudoisocyanine displays no shift in the presence of the ND particles; only small alteration of intensity is registered. These results support the significant role of the ND charge for adsorption of organic species such as fluorescent ions 21,27 and daunorubicin.…”
Section: Surface Charge Of the Colloidal Speciesmentioning
confidence: 94%
“…36 For CA 56 consisting of six phenyl units and bearing methyl at the lower rim, the ability to form aggregates with 60-200 nm in diameter in water solutions was observed even at lower concentration. 35 Attempts have also been made to synthesize and study CAs with amino groups attached to the lower rim. In particular, Martin et al 27 analyzed the self-aggregation of amphiphilic aminoCA 35 with a highly fluorinated upper rim and a lower rim functionalized with long moieties each containing an amido-and amino group.…”
Section: Reviewmentioning
confidence: 99%
“…Mchedlov-Petrossyan and co-workers found that the CAC of 64 decreased (4-0.12 mM) with increasing concentration of NaCl as well. 73 Similarly, the pH value could change the protonation states of hydrophilic heads, influencing charge interactions, resulting in a CAC change. Fujii and co-workers synthesized a new amphiphilic calix [4]arene 91 with hydrophilic amino end groups.…”
Section: Assembling Features Of Amphiphilic Calixarenes 221 Low Critical Aggregation Concentration (Cac)mentioning
confidence: 99%